(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2018)
This paper represented on the Deep learning technique growing in the learning community of machines, as traditional learning architecture has proven incompetent for the machine learning challenging tasks and strong feature of artificial intelligence (AI). Increasing and widespread availability of computing power, along the use of efficient training and improvement algorithms, has made it possible to implement, until then, the concept of deep learning. These development events deep learning architecture and algorithms look at cognitive neuroscience and point to biologically inspired solutions for learning. This paper represented on the rule of Convolutional Neural Networks (CNNs), Neural Networks (SNNs) and Hierarchical Temporary Memory (HTM), and other related techniques to the least mature technique.